MK2 Is Required for Neutrophil-Derived ROS Production and Inflammatory Bowel Disease - Zhang, Tao; Jiang, Junhang; Liu, Jingting; Xu, Lu; Duan, Shixin; Sun, Lei; Zhao, Wenjuan; Qian, Feng (Frontiers in Medicine, 2020)
Inflammatory bowel disease is a chronic disease that commonly accompanied by increased inflammatory responses and elevated reactive oxygen species of the gastrointestinal tract. Here, we found that MAPK-activated protein kinase 2 (MK2) modulates reactive oxygen species (ROS) production and is required for dextran sulfate sodium-induced inflammatory bowel disease in the mouse model. Genetic ablation of MK2 in the myeloid lineage cells (MK2Lyz2-KO) protected against DSS-induced colitis injury. In response to the DSS challenge, compared to MK2lyz2-WT mice, MK2Lyz2-KO mice exhibited less damage to epithelial and goblet cells, decreased generation of IL-6, TNF-α, and ROS, as well as reduced Ki67 positive cells and concentrations of Myeloperoxidase (MPO) in the intestinal epithelium. Furthermore, upon treatment with formylated peptide formyl-methionyl-leucylphenylalanine (fMLF), the generation of ROS was attenuated in MK2 deficient neutrophils, in which the phosphorylation of Akt and p38 MAPK was also reduced. Collectively, these findings indicated that MK2 is required for neutrophil-derived ROS production and inflammatory bowel disease, and MK2 and ROS are promising therapeutic targets for inflammatory bowel disease.